2019 IEEE 58th Conference on Decision and Control (CDC) 2019
DOI: 10.1109/cdc40024.2019.9029627
|View full text |Cite
|
Sign up to set email alerts
|

Economic model predictive control for snake robot locomotion

Abstract: In this work, the control of snake robot locomotion via economic model predictive control (MPC) is studied. Only very few examples of applications of MPC to snake robots exist and rigorous proofs for recursive feasibility and convergence are missing. We propose an economic MPC algorithm that maximizes the robot's forward velocity and integrates the choice of the gait pattern into the closed loop. We show recursive feasibility of the MPC optimization problem, where some of the developed techniques are also appl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the field of snake robots, Model Predictive Control is utilized for predictive path planning and automatic generation of locomotion. In [14], the economic MPC controller maximizes the robot's forward velocity while incorporating gate pattern selection in a closed-loop system. Experimental results demonstrate that the economic MPC algorithm surpasses a standard lateral undulation controller in terms of constraint satisfaction and overall performance.…”
Section: Model Predictive Control Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of snake robots, Model Predictive Control is utilized for predictive path planning and automatic generation of locomotion. In [14], the economic MPC controller maximizes the robot's forward velocity while incorporating gate pattern selection in a closed-loop system. Experimental results demonstrate that the economic MPC algorithm surpasses a standard lateral undulation controller in terms of constraint satisfaction and overall performance.…”
Section: Model Predictive Control Algorithmmentioning
confidence: 99%
“…Thus the algorithm shown in diagram 5 was named 'MPC-9'. A similar control strategy can be found in [14]. By leveraging the principles of serpentine motion and employing advanced control strategies, snake robots exhibit improved performance and agility, enabling them to navigate challenging environments with enhanced efficiency.…”
Section: Control Strategiesmentioning
confidence: 99%
“…However, there is a lack of visual implementation. Previous articles on the subject analyse the joint angles’ angular velocities and the robot’s head or mass centre linear velocity [ 24 , 25 , 26 , 27 , 28 ]. In these articles, snake robots used Line-of-Sight (LOS) guidance control law to exponentially stabilise the desired straight-line path under a given condition on the look-ahead distance parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the snake-like robot has the potential to experience body skidding. Some studies based on this assumption have been reported [5,6,7,8,9]. For example, in [9], body skidding is represented by a hybrid model to realize a propulsion control system.…”
Section: Introductionmentioning
confidence: 99%